The financial times guide to strategy how to create, pursue and deliver a winning strategy - Koch, Richard 1950- (Ascent Audio, 2024)
YOUR COMPLETE GUIDE TO STRATEGY. PLAIN AND SIMPLE. The Financial Times Guide to Strategy is your unbeatable reference on strategy. It offers an incisive overview of both corporate level and business unit level strategy, an A to Z of the world's leading strategic thinkers, and introduces the key strategic tools and techniques you need to develop your own strategy. Based on long experience and on conversations with leading strategists around the world, Richard Koch helps you discover each critical step in creating, delivering, and understanding successful strategy. The fifth edition of this bestselling book is your jargon-free guide to the strategic models and thinkers you really need to know about. Updated with new tools and examples, The Financial Times Guide to Strategy shows you which questions to ask, how to go about answering them, and then what action to take. This is the smartest and most accessible strategy guide available anywhere.